2021
DOI: 10.1590/acb360705
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid improves motor function induced by spinal cord injury in rats via inhibiting neuroinflammation and apoptosis

Abstract: Purpose To investigate the effect of ferulic acid (FA) on spinal cord injury (SCI)-induced motor dysfunction and to explore the possible pharmacological mechanisms. Methods Adult male Wistar rats were used in our study. SCI was achieved by clipping the spinal cord T9 of the rat by a vascular clip for 2 minutes. The motor function of the rat was evaluated by Basso, Beattie, and Bresnahan scoring method (BBB) and inclined plane test. Hematoxylin and eosin (HE) staining, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…Notably, compared to the other groups, there was a faster recovery of motor functions in the HSP-F/BCS group (Videos S1−S4). The improvement in functional recovery is comparable to previous studies, in which the effect of FA, 13,14 Buc 21 or HA-based hydrogel 43 was investigated separately in SCI repair. Although a trend in improved performance was reported in the HA-based hydrogel, it was not significant compared to the control.…”
Section: Cell Viability and Intracellular Ros Formationsupporting
confidence: 87%
See 2 more Smart Citations
“…Notably, compared to the other groups, there was a faster recovery of motor functions in the HSP-F/BCS group (Videos S1−S4). The improvement in functional recovery is comparable to previous studies, in which the effect of FA, 13,14 Buc 21 or HA-based hydrogel 43 was investigated separately in SCI repair. Although a trend in improved performance was reported in the HA-based hydrogel, it was not significant compared to the control.…”
Section: Cell Viability and Intracellular Ros Formationsupporting
confidence: 87%
“…Ferulic acid (FA) is a potent antioxidant, and its phenolic hydroxyl group can protect cells from oxidative stress. It could reduce the inflammatory responses induced by microglia. , It has been shown that FA could protect neurons after cerebral ischemic injury with anti-inflammatory and antioxidative effects . Yabe et al indicated that FA increases the proliferation of neural stem/progenitor cells (NSCs/NPCs) in vitro and in vivo , and improves stress-induced depressive behavior in mice .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we aim to further screen and develop candidate bioactive ingredient in the potential application against COVID-19 and ICH. Ferulic acid, a neuroprotective phytochemical, has exerted anti-inflammatory activity for protective action against nerve injury ( Jiang et al, 2021 ). In pharmacokinetic analysis in vivo using ultra-high performance liquid chromatography approach, the data show that the peak concentration of ferulic acid is 27.50 min under 0.199 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Like other polyphenolic compounds, the antioxidant properties of FA have been extensively reported (Graf 1992 ; Zduńska et al 2018 ). Moreover, FA has been observed to be effective in depression (Singh et al 2017 ; Liu et al 2017 ; Zeni et al 2017 ; Zheng et al 2019 ), neuroinflammation (Sun et al 2021 ; Jiang et al 2021 ; Singh 2017; Rehman et al 2019 ), neurodegeneration (Chaudhary et al 2019 ; Singh et al 2017 ; Sultana 2012 ), and cancer (Zduńska et al 2018 ). FA inhibits NF-κB, iNOS, COX-2 and modulates LPS-induced TLR4 pathway (Rehman et al 2019 ; Jung et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%